2011
DOI: 10.1371/journal.pgen.1002216
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis of Autoantibody Positivity in Type 1 Diabetes Cases

Abstract: The genetic basis of autoantibody production is largely unknown outside of associations located in the major histocompatibility complex (MHC) human leukocyte antigen (HLA) region. The aim of this study is the discovery of new genetic associations with autoantibody positivity using genome-wide association scan single nucleotide polymorphism (SNP) data in type 1 diabetes (T1D) patients with autoantibody measurements. We measured two anti-islet autoantibodies, glutamate decarboxylase (GADA, n = 2,506), insulinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
195
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(214 citation statements)
references
References 50 publications
(73 reference statements)
15
195
3
1
Order By: Relevance
“…This example shows that even for common polymorphisms, the EM approach can help to find likely associations that the naive approach can not. The SNP rs2476601 was found to be associated with T1D in several studies before the publication of [8] and was confirmed in a recent study in [29] that was published after the publication of [8]. All these studies support our results for the association of common polymorphisms with T1D.…”
Section: Resultssupporting
confidence: 89%
“…This example shows that even for common polymorphisms, the EM approach can help to find likely associations that the naive approach can not. The SNP rs2476601 was found to be associated with T1D in several studies before the publication of [8] and was confirmed in a recent study in [29] that was published after the publication of [8]. All these studies support our results for the association of common polymorphisms with T1D.…”
Section: Resultssupporting
confidence: 89%
“…Importantly, our study validated an association of chromosome 12q24.12. This locus was reported to be associated with CAD, 5 intracranial aneurysm, 14 ischemic stroke, 15 blood pressure, 16 kidney function, 17 type 1 diabetes, 18 serum urate 19 and lipid concentration, 20 and drinking behavior, 21 suggesting that this locus is an important genetic component of cardiovascular diseases and their risk factors. Because top associated SNP (rs3782886:A4G) is closely linked to two functional variants in this region (rs671:A4G in ALDH2 and rs11066001:C4T in BRAP), 22 we confirmed that the risk haplotype, which contains several functional variants, will affect the susceptibility of cardiovascular disease and its risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This CNVR is significantly heritable (P ¼ 6.35E-12), linked (P ¼ 0.045), and is flanked by SNPs associated with immunerelated functions. 22,23 A second of these 10 is a 370-bp CNVR within the first exon of the UGT1A7 gene. This CNVR is highly linked to its own genomic location (P ¼ 5.44E-60), and B6.6 kb from rs2602381, which was previously associated with attention-deficit hyperactivity disorder.…”
Section: Study Groupmentioning
confidence: 99%